2016
DOI: 10.1159/000447262
|View full text |Cite
|
Sign up to set email alerts
|

Hemoperitoneum Following Sexual Intercourse in a Woman with Deep Infiltrating Endometriosis

Abstract: Endometriosis is an estrogen-dependent chronic inflammatory disease, defined by the presence of endometrial glands and stroma at ectopic sites. A rare and life-threatening complication associated with endometriosis is represented by spontaneous hemoperitoneum due to the rupture of utero-ovarian vessels. Most cases of spontaneous hemoperitoneum previously described involved pregnant women affected by endometriosis; here, we present a case of acute and massive hemoperitoneum in a nulliparous woman with deep infi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…9 Additionally, Buggio et al reported that sexual intercourse could be a cause of utero-ovarian vessel rupture in a woman with endometriosis. 5 These reports suggest that chronic inflammation caused by endometriosis may render the pelvic vessels more friable, and physical stretching of the endometrial adhesion caused by menstruation or sexual intercourse may result in vessel rupture. In the present case, severe endometriotic adhesions were extensively observed as a characteristic finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 Additionally, Buggio et al reported that sexual intercourse could be a cause of utero-ovarian vessel rupture in a woman with endometriosis. 5 These reports suggest that chronic inflammation caused by endometriosis may render the pelvic vessels more friable, and physical stretching of the endometrial adhesion caused by menstruation or sexual intercourse may result in vessel rupture. In the present case, severe endometriotic adhesions were extensively observed as a characteristic finding.…”
Section: Discussionmentioning
confidence: 99%
“…Both cases had spontaneous acute hemoperitoneum from the uterine artery eroded by an endometriotic lesion; wherein, one case was asymptomatic and occurred during menstruation 9 . Additionally, Buggio et al reported that sexual intercourse could be a cause of utero‐ovarian vessel rupture in a woman with endometriosis 5 . These reports suggest that chronic inflammation caused by endometriosis may render the pelvic vessels more friable, and physical stretching of the endometrial adhesion caused by menstruation or sexual intercourse may result in vessel rupture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the two reported cases of kidney endometriotic implants, endometriosis was never considered a possible aetiology for the symptoms. Interestingly, Buggio et al (2016) and Togami et al (2015) reported two cases of haemoperitoneum, one spontaneous and one after sexual intercourse, in which endometriosis was not suspected until exploratory surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients had already received a diagnosis of endometriosis either at diagnostic laparoscopy or ultrasound (Janicki et al 2002;Togami et al 2015). The haemoperitoneum was spontaneous in two cases, whereas in one patient, it occurred just after sexual intercourse (Buggio et al 2016).…”
Section: Haemoperitoneummentioning
confidence: 99%